Implementation of Competitive Strategy, Competitive Area, Competitive Result in Increasing the Competitiveness of Islamic Education Marketing - Huzali, Ikhsan; Setiawan, Andi; Purnomo, Muhammad Sidiq; Ishak, Nor Syahidah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to describe competitive strength, competitive area, and Competitive Result in increasing the competitiveness of Islamic education marketing. This type of research is categorized as literature research and examines the strength of competition, A person's competitiveness is affected by many factors, including the strength of competition. The quality of education is an important component. Students will have an exceptional learning experience in an educational institution that has a relevant curriculum, experienced teachers, and effective teaching methods. The market targeted by educational institutions can be considered as a competitive market. In order for an educational institution's marketing and development strategy to work well, it is important to accurately identify and understand these areas of competition. In Islamic educational institutions, competitive outcomes include achievements and outcomes intended to increase competitiveness. The strategic goal of competitive outcomes is to gain an edge over the competition, drive growth, and guarantee the institution's long-term success.